Histopathological Test of Placental Tissue to Measure the Effectiveness of Mahkota Dewa Fruit (Phaleria Macrocarpa) in Overcoming Placental Inflammation in Case of Preeclampsia - Eftyaningrum Dwi Wahyu Astutik; Wiwit Vitania; Yustika Rahmawati Pratami; Hasnia Hasnia; Lilian Stevanie Verlina Bakarbessy (GLOBAL HEALTH SCIENCE GROUP, 2026)
Preeclampsia is disturbance pregnancy - related hypertension​ close with inflammation placenta, stress oxidative, and damage structure network placenta that has an impact bad to health mother and fetus. Available therapies​ moment This Still focus on control symptoms and not yet in a way specific target mechanism base in the form of inflammation placenta. Fruit The Crown of God (Phaleria macrocarpa) is plant drug original Indonesian containing compound bioactive potential anti-inflammatory, but proof scientific about its effectiveness to inflammation placenta in preeclampsia Still limited. Research objectives This For test effectiveness extract fruit Crown of the Gods in lower inflammation placenta based on description histopathology network placenta in preeclampsia model. Research methods This use design true experimental post-test only control group in mice white female induced pregnancy (Rattus norvegicus) preeclampsia using monosodium glutamate. Subject study shared become six group, namely normal control, control preeclampsia, control nifedipine comparator, as well as three group treatment extract ethanol fruit Crown of the Gods with doses of 180, 360, and 720 mg/ kgBW. Tissue placenta taken after delivery and examination in a way histopathology use coloring hematoxylin -eosin with infiltration parameters cell inflammation, edema, necrosis, degeneration trophoblast, and cell structure. Data were analyzed using one ANOVA test direction and Tukey's further test. The results of the study show that induction preeclampsia cause improvement inflammation real placenta, whereas​ giving extract fruit Crown of the Gods in a way significant lower degrees inflammation placenta. Dose 360 mg/ kgBW show effectiveness best with description histopathology that approaches normal conditions. It was concluded that fruit The Crown of God is proven effective lower degrees damage histopathological placenta in a way significant in the preeclampsia model.